Efikasi Diri Dan Kecerdasan Emosional Dimoderasi Dukungan Orang Tua Terhadap Adaptabilitas Karier - Wijayanti, Tata Dwi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The objective of this research is to explain the effects of self-efficacy and emotional quotient on the career adaptability of students of Faculty of Economics and Business of Universitas Brawijaya batch of 2020 who are writing their minor thesis with the moderation of parental support. Using probability sampling, 90 people were selected as the sample of this explanatory research. the data was harvested through Likert-scaled questionnaires, processed and analyzed in SPSS version 25. This study finds that (1) self-efficacy and emotional quotient simultaneously have significant effects on the students’ career adaptability, (2) that self-efficacy significantly influences the students’ career adaptability, (3) that emotional quotient significantly affects the students’ career adaptability, and that (4) parental support does not moderate the effects of both self-efficacy and emotional quotient on the students’ career adaptability. In addition, this research results in the coefficient of determination of 64% on the career adaptability of students of Faculty of Economics and Business batch of 2020 who are writing their minor thesis. Abstrak Penelitian ini bertujuan untuk menjelaskan pengaruh efikasi diri dan kecerdasan emosional yang dimoderasi oleh dukungan orang tua terhadap adaptabilitas karier mahasiswa Angkatan 2020 Fakultas Ekonomi dan Bisnis Universitas Brawijaya yang sedang menyusun skripsi. Penelitian ini merupakan penelitian explanatory research yang menggunakan teknik sampling yaitu probability sampling. Sampel yang digunakan sebanyak 90 orang dan menggunakan SPSS versi 25 dalam mengolah dan menganalisis data, dengan menggunakan skala likert. Hasil penelitian ini menunjukkan bahwa: (1) Efikasi diri dan kecerdasan emosional memiliki pengaruh signifikan secara simultan terhadap adaptabilitas karier mahasiswa, (2) Efikasi diri memiliki pengaruh signifikan terhadap adaptabilitas karier mahasiswa, (3) Kecerdasan emosional memiliki pengaruh signifikan terhadap adaptabilitas karier mahasiswa, (4) Dukungan orang tua tidak mampu memoderasi pengaruh efikasi diri maupun kecerdasan emosional terhadap adaptabilitas karier mahasiswa. Penelitian ini mengungkapkan hasil koefisien determinasi sebesar 64,8% terhadap adaptabilitas karier mahasiswa Angkatan 2020 Fakultas Ekonomi dan Bisnis yang sedang menyusun skripsi.